125 Utilization of Performance-tested and NSIP Sires Improved Progeny Performance and Value in Ram Test Program. (8th March 2022) - Weaver, Andrew R; Wright, Donald L; Greiner, Scott P
Abstract: Sire selection can have long-term impacts on flock performance. The objective here was to evaluate the effect of performance-tested and/or NSIP rams on progeny performance and value in a ram test program. Rams (Katahdin = 104, Dorper = 7, Texel = 3, Cheviot = 3) were delivered to the Southwest Virginia Agricultural Research and Extension Center (SWAREC) Ram Test on June 1. Ram pedigrees were obtained from consignors and rams were classified based on whether their sires were tested in a previous SWAREC Ram Test (TESTED), enrolled in the National Sheep Improvement Program (NSIP), or neither TESTED nor NSIP (NEITHER). Some sires (16%) were previously tested and enrolled in NSIP. Rams were dewormed and rested for two weeks. On June 22, rams were given Haemonchus contortus larvae adjusted for body weight (average = 5000 L3). FAMACHA scores and fecal egg counts (FEC) were monitored every two weeks until August 31. Rams were dewormed based on FAMACHA ≥ 3. Select rams were sold at auction as breeding stock. Statistical analysis were performed using SAS (SAS Institute, Cary, NC). Rams requiring deworming had greater FAMACHA scores and FEC at all time points (P < 0.05), despite not requiring treatment until August 17 (5%) and August 31 (12%). In total, 17% of rams were dewormed. Of the dewormed rams, a smaller portion of rams sired by TESTED rams (10%) and NSIP rams (15%) required treatment compared to rams sired by NEITHER rams (85%; P < 0.05). Rams sired by TESTED and NSIP rams had a higher average value than those sired by NEITHER rams (2070 and 1838, respectively, vs. 1078; P < 0.05). Selection of sires that are TESTED and/or NSIP resulted in progeny that had a lesser chance of requiring treatment and sold for greater value.